Talking SMAAC: A New Tool to Measure Soil Respiration and Microbial Activity - Joshi Gyawali, Ayush; Lester, Brandon J.; Stewart, Ryan D. (Frontiers in Earth Science, 2019)
Soil respiration measurements are widely used to quantify carbon fluxes and ascertain soil biological properties related to soil microbial ecology and soil health, yet current methods to measure soil respiration either require expensive equipment or use discrete spot measurements that may have limited accuracy and neglect underlying response dynamics. To overcome these drawbacks, we developed an inexpensive setup for measuring CO2 called the Soil Microbial Activity Assessment Contraption (SMAAC). We then compared SMAAC with a commercial Infrared Gas Analyzer (IRGA) unit by analyzing a soil that had been subjected to two different management practices: grass buffer versus row crop cultivation with tillage. These comparisons were done using three configurations that detected 1) in situ soil respiration, 2) CO2 burst tests, and 3) substrate induced respiration, a measure of active microbial biomass. The SMAAC provided consistent readings with the commercial IRGA unit for all three configurations tested, showing that the SMAAC can perform well as an inexpensive yet accurate tool for measuring soil respiration and microbial activity.